PEMBELAJARAN MATEMATIKA REALISTIK PADAMATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT BAGI SISWA KELAS IV SEKOLAH DASAR - Kurniawati, Rissa Prima (Premiere Educandum, 2015)
Mathematics has characteristic in good abstract object. That cause students have difficulty in understanding of mathematics. Therefore, thereal-lifeexperiences ofchildrenin the classroom are important for learning and students will understand thematerial quickly. This study is aimed to describe the activities of students during thelearning process that takes place in the material realistic arithmetic addition andsubtraction and describe the learning completeness students after being taught withrealistic learning the material arithmetic addition and subtraction of integers. This typeof research used in this research is qualitative research. Subjects in this study werestudents of class IV SDN Jenangan, Kwadungan, Ngawi. Based on this research, studentactivities relevant to teaching (teaching and learning) of 98.83% classified in thecategory very well. While the student activity whichis not relevant to the teaching of10.15%. Completeness students in realistic mathematics learning on the materialarithmetic operations of addition and subtraction of integers for fourth grade students ofSDN Jenangan, Kwadungan, Ngawi gained mastery learning students individually of 12students from the number of students as many as 15 students altogether, whichis notcompleted individually as 3 students. While the classical completeness, acquired 80% ofstudents who completed study. Keywords: Learning, Realistic Mathematics